Spinal Dysraphism of a Baby A Case Report (BIRDEM Medical Journal, 2016)
A 8 months old male child reported to paediatric OPD of Shaheed Suhrawardy Medical College Hospital with the complaints of small swelling in the back and tilting of body on one side during sitting and standing posture. His antenatal period was unremarkable, post natal period revealed delayed crying and immunization was not completed. Local examination showed a small hairy patch in lower dorsal region. General and systemic examination revealed no significant abnormality. Consulting physician advised to do X- ray of dorso- lumbar spine (both views), Ultrasonography (USG) of the swelling and FNAC from the swelling. X- ray report concluded as spinal dysraphism with widening of spinal canal. Ultrasonography showed dural ectasia. No malignant or granulomatous cells were found in FNAC. For confirmation of plain x- ray and USG findings, the patients parent was advised to do MRI of dorsolumbar spine in Radiology and Imaging Department of BIRDEM hospital. MRI findings were compatible with Diastematomyelia with tethered cord as evidenced by two unequal hemicord separated by signal void cleft and low insertion of spinal cord at L4-L5 level. As MRI is less sensitive regarding bone , CT scan was done and CT revealed grossly abnormal vertebral bodies with an osseous spur traversing the entire canal dividing the canal into two halves. Spinal cord was also divided into two unequal cord. Considering X-ray, USG, CT and MRI, final Diagnosis was made as Type I Diastematomyelia with Tethered cord.Birdem Med J 2015; 5(1): 42-45